Representation distortion contributes to agreement attraction in comprehension - Keshev, Maayan; Cartner, Mandy; Meltzer-Asscher, Aya; Dillon, Brian (Frontiers in Language Sciences, 2026)
Sentence comprehension relies on encoding linguistic items in memory and accessing them subsequently to form linguistic dependencies. This makes processing susceptible to memory interference. Interference, such as the distortion of memory representations or access to irrelevant memory items, can lead to misinterpretation or grammatical errors. Over the years, research on agreement attraction has debated whether this hallmark of memory interference reflects limits of the retrieval mechanism, or inaccuracy of the encoded representations that retrieval targets. We present some evidence in favor of representational accounts of memory interference. Our findings include partial evidence for three kinds of representational effects: (a) the ungrammaticality illusion, a pattern by which attraction arises without misleading retrieval cues; (b) number errors rather than noun errors in final interpretation; and (c) mitigation of attraction when additional markers of the subject's number are available, which we label feature updating. Together, the findings seem to suggest that feature distortion in the content of memory representations contributes to attraction effects. We propose that models of memory mechanisms that mediate dependency formation should incorporate malleable representations rather than stable ones.